Anthropological-Psychological Approaches to Enhancing Literacy on Sexual Behavior Deviations for Preventing Mental Health Disorders - Nurul Kariimah; Hamka Naping; Safriadi Safriadi; Irfan Kurniawan (Endogami: Jurnal Ilmiah Kajian Antropologi, 2025)
Sexual behavior deviations represent a multidimensional issue closely linked to social norms, cultural constructions, and individual psychological experiences. Low levels of sexual literacy in workplace settings often generate stigma, misinterpretations, and increase the risk of mental health problems. This study aimed to evaluate the effectiveness of socialization programs addressing deviant sexual behavior in organizational contexts by employing a psychological anthropology approach, emphasizing the role of work culture in shaping understanding and supporting preventive efforts. A total of 20 employees from Company X in Makassar participated in a 60-minute session using the Participatory Rural Appraisal (PRA) method designed to foster active engagement. The materials were developed collaboratively, highlighting psychological aspects, local cultural values, organizational dynamics, and their relevance to mental health prevention. Pre- and post-test results demonstrated a significant improvement, with average scores increasing from 65 to 83; 80% of participants achieved a high level of understanding, while the remainder fell into medium and low categories. These findings confirm that a work culture–based psychological anthropology approach effectively enhances literacy on deviant sexual behavior and should be integrated into human resource development policies as an adaptive promotive-preventive strategy for managing cultural diversity in modern organizations.